Hydrogen sulfide attenuates ferric chloride-induced arterial thrombosis in rats. (2nd June 2016) - Qin, Yi-Ren; You, Shou-Jiang; Zhang, Yan; Li, Qian; Wang, Xian-Hui; Wang, Fen; Hu, Li-Fang; Liu, Chun-Feng
ABSTRACT: Hydrogen sulfide (H2 S) is a novel gaseous transmitter, regulating a multitude of biological processes in the cardiovascular and other systems. However, it remains unclear whether it exerts any effect on arterial thrombosis. In this study, we examined the effect of H2 S on ferric chloride (FeCl3 )-induced thrombosis in the rat common carotid artery (CCA). The results revealed a decrease of the H2 S-producing enzyme cystathionine γ-lyase (CSE) expression and H2 S production that persisted until 48 h after FeCl3 application. Intriguingly, administration with NaHS at appropriate regimen reduced the thrombus formation and enhanced the blood flow, accompanied with the alleviation of CSE and CD31 downregulation, and endothelial cell apoptosis in the rat CCA following FeCl3 application. Moreover, the antithrombotic effect of H2 S was also observed in Rose Bengal photochemical model in which the development of thrombosis is contributed by oxidative injury to the endothelium. The in vitro study demonstrated that the mRNA and protein expression of CSE, as well as H2 S production, was decreased in hydrogen peroxide (H2 O2 )-treated endothelial cells. Exogenous supplement of NaHS and CSE overexpression consistently alleviated the increase of cleaved caspase-3 and endothelial cell damage caused by H2 O2 . Taken together, our findings suggest that endogenous H2 S generation in the endothelium may be impaired during arterial thrombosis and that modulation of H2 S, either exogenous supplement or boost of endogenous production, may become a potential venue for arterial thrombosis therapy.